Peptide Receptor Radionuclide Therapy (PRRT) with 177Lu-DOTATATE; Differences in Tumor Dosimetry, Vascularity and Lesion Metrics in Pancreatic and Small Intestinal Neuroendocrine Neoplasms - Ulrika Jahn (Cancers, 2021)
Dosimetry during peptide receptor radionuclide therapy (PRRT) has mainly focused on normal organs and less on the tumors. The absorbed dose in one target tumor per patient and several response related factors were assessed in 23 pancreatic neuroendocrine neoplasms (P-NENs) and 25 small-intestinal NEN (SI-NENs) during PRRT with 177Lu-DOTATATE. The total administered activity per patient was (mean ± standard error of mean (SEM) 31.8 ± 1.9 GBq for P-NENs and 36 ± 1.94 GBq for SI-NENs. The absorbed tumor dose was 143.5 ± 2 Gy in P-NENs, 168.2 ± 2 Gy in SI-NENs. For both NEN types, a dose–response relationship was found between the absorbed dose and tumor shrinkage, which was more pronounced in P-NENs. A significant drop in the absorbed dose per cycle was shown during the course of PRRT. Tumor vascularization was higher in P-NENs than in SI-NENs at baseline but equal post-PRRT. The time to progression (RECIST 1.1) was similar for patients with P-NEN (mean ± SEM 30 ± 1 months) and SI-NEN (33 ± 1 months). In conclusion, a dose response relationship was established for both P-NENs and SI-NENs and a significant drop in the absorbed dose per cycle was shown during the course of PRRT, which warrants further investigation to understand the factors impacting PRRT to improve personalized treatment protocol design.